Epitaxial growth and characterization of GaN films on 6H-SiC by MOVPE - Nam, OH; Kim, GH; Park, D; Yoo, JB; Kum, DW (IOP PUBLISHING LTD, 1996)
Metalorganic vapor phase epitaxial growth and characterization of GaN layers on vicinal 6H-SiC(0001) substrates are reported. GaN films have been grown at 1020 degrees C and atmospheric pressure using trimethylgallium(TMG) and NH3 in an IR lamp heated horizontal reactor. GaN films have optically flat surfaces free from cracks, and cross-sectional TEM has revealed that GaN films have relatively small number of defects such as dislocations and stacking faults near the GaN/SiC interface. The epitaxial relationship between GaN and SiC was (0001)GaN//(0001)SiC and the interface was highly coherent. Double crystal X-ray rocking curve(DCXRC) measurements on GaN films have revealed full width at half maximum(FWHM) values as low as 249 arcsec for GaN(0002) peak without correcting the instrumental broadening effects. Cross-sectional TEM and XRC results indicate that the crystal quality of GaN directly grown on SiC(0001) without a buffer layer is comparable to that of GaN with a buffer layer on sapphire(0001) substrates. Low temperature(T = 11 K) PL spectra of the GaN films grown to date were dominated by the near-band-gap emission band with the maximum at 358 nm(3.46 eV).
Keywords: AIN BUFFER LAYER; SAPPHIRE